Update simple sequence summation proofs as verified.
parent
0744023a9d
commit
1cff1c63c4
|
@ -13,32 +13,125 @@
|
||||||
\section{Summations}%
|
\section{Summations}%
|
||||||
\label{sec:summations}
|
\label{sec:summations}
|
||||||
|
|
||||||
\subsection{\unverified{Arithmetic Series}}%
|
\subsection{\verified{Arithmetic Series}}%
|
||||||
\label{sub:sum-arithmetic-series}
|
\label{sub:sum-arithmetic-series}
|
||||||
|
|
||||||
Let $(a_i)_{i \geq 0}$ be an arithmetic sequence with common difference $d$.
|
Let $(a_i)_{i \geq 0}$ be an arithmetic sequence with common difference $d$.
|
||||||
Then for some $n \in \mathbb{N}$,
|
Then for some $n \in \mathbb{N}$,
|
||||||
$$\sum_{i=0}^n a_i = \frac{(n + 1)(a_0 + a_n)}{2}.$$
|
\begin{equation}
|
||||||
|
\label{sub:sum-arithmetic-series-eq1}
|
||||||
|
\sum_{i=0}^n a_i = \frac{(n + 1)(a_0 + a_n)}{2}.
|
||||||
|
\end{equation}
|
||||||
|
|
||||||
\begin{proof}
|
\begin{proof}
|
||||||
|
|
||||||
\lean{Common/Real/Sequence/Arithmetic}
|
\lean{Common/Real/Sequence/Arithmetic}
|
||||||
{Real.Arithmetic.sum\_recursive\_closed}
|
{Real.Arithmetic.sum\_recursive\_closed}
|
||||||
|
|
||||||
|
\divider
|
||||||
|
|
||||||
|
Let $(a_i)_{i \geq 0}$ be an arithmetic sequence with common difference $d$.
|
||||||
|
By definition, for all $k \in \mathbb{N}$,
|
||||||
|
\begin{equation}
|
||||||
|
\label{sub:sum-arithmetic-series-eq2}
|
||||||
|
a_k = (a_0 + kd).
|
||||||
|
\end{equation}
|
||||||
|
Define predicate $P(n)$ as "identity \eqref{sub:sum-arithmetic-series-eq1}
|
||||||
|
holds for value $n$."
|
||||||
|
We use induction to prove $P(n)$ holds for all $n \geq 0$.
|
||||||
|
|
||||||
|
\paragraph{Base Case}%
|
||||||
|
|
||||||
|
Let $k = 0$.
|
||||||
|
Then $$\sum_{i=0}^k a_i = a_0 = \frac{2a_0}{2} =
|
||||||
|
\frac{(k + 1)(a_0 + a_k)}{2}.$$
|
||||||
|
Therefore $P(0)$ holds.
|
||||||
|
|
||||||
|
\paragraph{Induction Step}%
|
||||||
|
|
||||||
|
Assume induction hypothesis $P(k)$ holds for some $k \geq 0$.
|
||||||
|
Then
|
||||||
|
\begin{align*}
|
||||||
|
\sum_{i=0}^{k+1} a_i
|
||||||
|
& = \sum_{i=0}^k a_i + a_{k+1} \\
|
||||||
|
& = \frac{(k + 1)(a_0 + a_k)}{2} + a_{k+1}
|
||||||
|
& \text{induction hypothesis} \\
|
||||||
|
& = \frac{(k + 1)(a_0 + (a_0 + kd))}{2} + (a_0 + (k + 1)d)
|
||||||
|
& \eqref{sub:sum-arithmetic-series-eq2} \\
|
||||||
|
& = \frac{(k + 1)(2a_0 + kd)}{2} + (a_0 + (k + 1)d) \\
|
||||||
|
& = \frac{(k + 1)(2a_0 + kd) + 2a_0 + 2(k + 1)d}{2} \\
|
||||||
|
& = \frac{2ka_0 + k^2d + 4a_0 + kd + 2kd + 2d}{2} \\
|
||||||
|
& = \frac{(k + 2)(2a_0 + kd + d)}{2} \\
|
||||||
|
& = \frac{(k + 2)(a_0 + a_0 + (k + 1)d)}{2} \\
|
||||||
|
& = \frac{(k + 2)(a_0 + a_{k+1})}{2}
|
||||||
|
& \eqref{sub:sum-arithmetic-series-eq2} \\
|
||||||
|
& = \frac{((k + 1) + 1)(a_0 + a_{k+1})}{2}.
|
||||||
|
\end{align*}
|
||||||
|
Thus $P(k)$ implies $P(k + 1)$ holds true.
|
||||||
|
|
||||||
|
\paragraph{Conclusion}%
|
||||||
|
|
||||||
|
By mathematical induction, it follows for all $n \geq 0$, $P(n)$ is true.
|
||||||
|
|
||||||
\end{proof}
|
\end{proof}
|
||||||
|
|
||||||
\subsection{\unverified{Geometric Series}}%
|
\subsection{\verified{Geometric Series}}%
|
||||||
\label{sub:sum-geometric-series}
|
\label{sub:sum-geometric-series}
|
||||||
|
|
||||||
Let $(a_i)_{i \geq 0}$ be a geometric sequence with common ratio $r \neq 1$.
|
Let $(a_i)_{i \geq 0}$ be a geometric sequence with common ratio $r \neq 1$.
|
||||||
Then for some $n \in \mathbb{N}$,
|
Then for some $n \in \mathbb{N}$,
|
||||||
$$\sum_{i=0}^n a_i = \frac{a_0(1 - r^{n+1})}{1 - r}.$$
|
\begin{equation}
|
||||||
|
\label{sub:sum-geometric-series-eq1}
|
||||||
|
\sum_{i=0}^n a_i = \frac{a_0(1 - r^{n+1})}{1 - r}.
|
||||||
|
\end{equation}
|
||||||
|
|
||||||
\begin{proof}
|
\begin{proof}
|
||||||
|
|
||||||
\lean{Common/Real/Sequence/Geometric}
|
\lean{Common/Real/Sequence/Geometric}
|
||||||
{Real.Geometric.sum\_recursive\_closed}
|
{Real.Geometric.sum\_recursive\_closed}
|
||||||
|
|
||||||
|
\divider
|
||||||
|
|
||||||
|
Let $(a_i)_{i \geq 0}$ be a geometric sequence with common ratio $r \neq 1$.
|
||||||
|
By definition, for all $k \in \mathbb{N}$,
|
||||||
|
\begin{equation}
|
||||||
|
\label{sub:sum-geometric-series-eq2}
|
||||||
|
a_k = a_0r^k.
|
||||||
|
\end{equation}
|
||||||
|
Define predicate $P(n)$ as "identity \eqref{sub:sum-geometric-series-eq1}
|
||||||
|
holds for value $n$."
|
||||||
|
We use induction to prove $P(n)$ holds for all $n \geq 0$.
|
||||||
|
|
||||||
|
\paragraph{Base Case}%
|
||||||
|
|
||||||
|
Let $k = 0$.
|
||||||
|
Then $$\sum_{i=0}^k a_i = a_0 = \frac{a_0(1 - r)}{1 - r} =
|
||||||
|
\frac{a_0(1 - r^{k+1})}{1 - r}$$
|
||||||
|
Therefore $P(0)$ holds.
|
||||||
|
|
||||||
|
\paragraph{Induction Step}%
|
||||||
|
|
||||||
|
Assume induction hypothesis $P(k)$ holds for some $k \geq 0$.
|
||||||
|
Then
|
||||||
|
\begin{align*}
|
||||||
|
\sum_{i=0}^{k+1} a_i
|
||||||
|
& = \sum_{i=0}^k a_i + a_{k+1} \\
|
||||||
|
& = \frac{a_0(1 - r^{k+1})}{1 - r} + a_{k + 1}
|
||||||
|
& \text{induction hypothesis} \\
|
||||||
|
& = \frac{a_0(1 - r^{k+1})}{1 - r} + a_0r^{k + 1}
|
||||||
|
& \eqref{sub:sum-geometric-series-eq2} \\
|
||||||
|
& = \frac{a_0(1 - r^{k+1}) + a_0r^{k+1}(1 - r)}{1 - r} \\
|
||||||
|
& = \frac{a_0(1 - r^{k+1} + r^{k+1}(1 - r))}{1 - r} \\
|
||||||
|
& = \frac{a_0(1 - r^{k+1} + r^{k+1} - r^{k+2})}{1 - r} \\
|
||||||
|
& = \frac{a_0(1 - r^{k+2})}{1 - r} \\
|
||||||
|
& = \frac{a_0(1 - r^{(k + 1) + 1})}{1 - r}.
|
||||||
|
\end{align*}
|
||||||
|
Thus $P(k)$ implies $P(k + 1)$ holds true.
|
||||||
|
|
||||||
|
\paragraph{Conclusion}%
|
||||||
|
|
||||||
|
By mathematical induction, it follows for all $n \geq 0$, $P(n)$ is true.
|
||||||
|
|
||||||
\end{proof}
|
\end{proof}
|
||||||
|
|
||||||
\end{document}
|
\end{document}
|
||||||
|
|
Loading…
Reference in New Issue